Strategies and technologies for developing online computer labs for technology-based courses - Chao, Lee 1951- (Gale virtual reference library, 2008)
"Discusses design strategies, implementation difficulties, and the effectiveness of online labs. Provides scholars, researchers, and practitioners support for lab-based e-learning, gives guidance on the selection of technologies for various projects, and illustrates Web-based teaching with case studies"--Provided by publisher.